Polar Patrol Balloon experiment during 1991-1993 - Ryoichi Fujii; Hiroshi Miyaoka; Akira Kadokura; Ono Takayuki; Hisao Yamagishi; Natsuo Sato; Masaki Ejiri; Takeo Hirasawa; Jun Nishimura; Nobuyuki Yazima; Takamasa Yamagami; Shigeo Ohta; et al. (National Institute of Polar Research, 1989)
Since 1984 the National Institute of Polar Research, the Institute of Space and Astronautical Science and collaborative scientists have conducted the long-term circumpolar balloon program that is called Polar Patrol Balloon (PPB) project, and they also have developed ballooning technologies for this program. This project aims at establishing a station network in the stratosphere over the Antarctic region for geophysical and astrophysical observations. Two test flight experiments that were performed by the 28th Japanese Antarctic Research Expedition (JARE) in 1987 have convinced us that PPB would come back to the launching area with a good possibility. During 1991 and 1993 (JARE-32-34) at Syowa Station. The PPB experiments will consequently be done for scientific researches. This brief paper reports unique advantages of PPB, specifications and expected trajectories of PPB, and planned scientific researches with PPB.